Artificial Intelligence (AI) and Digital Technology Roles in Enhancing Self-Care Among Hypertensive Patients Globally: A Scoping Review - Nurul Khusnul; Musdalifah Mukhtar (LPPM STIKES Mataram, 2026)
Introduction: Hypertension remains a critical 21st-century global health challenge, characterized by suboptimal blood pressure control rates. Conventional self-care practices are frequently hindered by recall bias and poor patient retention (app fatigue). Objective: This study aims to map the types of digital technologies and AI modalities utilized in enhancing self-care. Methods: This scoping review explores global scientific evidence sourced from PubMed, Scopus, Embase, CINAHL, and Google Scholar databases up to early 2026. Results: The most frequently intervened self-care domains were automated self-measurement of blood pressure, medication adherence reminders, alongside DASH diet management and physical activity tracking. Conclusion: AI integration is revolutionizing hypertension management, shifting it from passive monitoring to proactive virtual companionship that effectively stabilizes patient hemodynamics.